2021
DOI: 10.5539/jas.v13n12p71
|View full text |Cite
|
Sign up to set email alerts
|

Broccoli Production With Regulated Deficit Irrigation at Different Phenological Stages

Abstract: The objective of this study was to evaluate the effects of different levels of soil water replacement in each phenological stage of broccoli crop cultivated in a protected environment. The experiment was conducted in a protected environment in the municipality of Maringá, Paraná, Brazil. The experimental design used was in randomized blocks 4 by 3 having four levels of water replacement (55, 70, 85, and 100% of crop evapotranspiration) applied in three phenological stages (initial, interm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…Several studies have reported water reduction impacts in agricultural crops [4,14,[31][32][33][34]. In this study, the effect of Ascophyllum nodosum extract applications in different doses by fertigation during the tomato crop cycle (Tucaneiro hybrid) was evaluated under two different irrigation conditions (100% of ETc and 70% of ETc), in order to analyze the impacts on plant growth, fruit yield, physiological aspects and fruit quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported water reduction impacts in agricultural crops [4,14,[31][32][33][34]. In this study, the effect of Ascophyllum nodosum extract applications in different doses by fertigation during the tomato crop cycle (Tucaneiro hybrid) was evaluated under two different irrigation conditions (100% of ETc and 70% of ETc), in order to analyze the impacts on plant growth, fruit yield, physiological aspects and fruit quality.…”
Section: Discussionmentioning
confidence: 99%
“…Regulated deficit irrigation enhances some secondary metabolites such as carotenoids and phenolic components in plant tissues [6], affecting tomato nutritional value, mainly due to an antioxidant activity increase in tomatoes [9]. High total polyphenols from tomato under moderate water stress could resulted from a defense strategy against this abiotic stress [32]. Less water availability for tomato crop absorption could have resulted in a higher soluble solid concentration and consequently presented fruit with a better flavor ratio [14,41].…”
Section: Discussionmentioning
confidence: 99%
“…Deficit irrigation strategy is an agronomic approach for improving water-use efficiency and water management in irrigated agriculture [1]. This strategy consists of performing irrigation with an amount of water below the amount demanded by the crops, which may be during certain periods of growth, such as initial stages or low water demand [2], or even throughout the entire cycle [3]. The main advantage of deficit irrigation is water savings, especially in regions with water scarcity or where water is a limited resource [4].…”
Section: Introductionmentioning
confidence: 99%
“…Various techniques and management tools can be employed to alleviate the impacts of water stress on plants. These encompass controlled water restriction during less sensitive stages (Terassi et al, 2021), the interval between water replacements (Santos et al, 2021), nutritional management (Saath et al, 2022), and the application of beneficial elements (Lozano et al, 2018;Hachmann et al, 2019).…”
Section: Introductionmentioning
confidence: 99%